Glasgow Coma Scale (GCS): Multicenter Validation Study of Psychometric Properties of the Official Russian Version - M. A. Piradov; N. A. Suponeva; K. A. Yatsko; D. G. Yusupova; A. A. Zimin; L. A. Legostayeva; E. G. Yazeva; M. A. Domashchenko; V. Yu. Samorukov; A. A. Belkin; E. A. Kondratyeva; S. A. Kondratyev; et al. (Неотложная медицинская помощь)
OBJECTIVE. Assessment of patients with impaired consciousness is a priority task in the department intensive care. The Glasgow Coma Scale (GCS), which includes assessment of motor , speech and ocular reactions, was the first scale developed for this purpose. The absence of versions of the GCS that passed validation research, reduces quality of its application in Russia and other Russian-speaking countries and limits the possibility of obtaining objective clinical results during evaluation patients with reduced level of wakefulness, significantly decreased availability of the scale for scientific and clinical use.AIM OF STUDY. Rating psychometric parameters of the Glasgow Coma Scale as part of the 2nd stage of the multicenter validation research.MATERIAL AND METHODS. In a group of 171 patients over 18 years old with different levels decreased wakefulness, as well as in clear consciousness, hospitalized in the department resuscitation and intensive care therapy performed assessment psychometric properties (reliability, validity, sensitivity).RESULTS. For the Russian version of the GCS received high levels of validity (p<0.0001, Spearman correlation coefficient r=0.91), reliability (p<0.001, coefficient correlations Spearman r=0.88; p<0.0001, Cronbach’s alpha coefficient α=0.78; p<0.001, Cohen’s kappa coefficient κ=0.74) and sensitivity (Wilcoxon test p=0.426 in the main group and Wilcoxon test p=0.782 in the group “without speech function assessment”).CONCLUSION. In the conducted research demonstrated a sufficient level psychometric properties of the Russian version of the Glasgow Coma Scale, which opens up the possibility of its application in Russia and Russian-speaking countries. The scale is available for downloading on the Validation Group website international scales and questionnaires of the Federal State Budgetary Scientific Institution Scientific Center of Neurology.